Ateliers 1984. - Bargues, Christoph; Brandely, Daniel; Lamarche-Vadel, Bernard; Obalk, Hector; Pagnoux, Michel; Pagé, Suzanne; Roche, Jean-Claude; Tió Bellido, Ramon (Paris : ARC Musée d'Art Moderne de la Ville de Paris, 1984)
Agid, Olivier ; Aoun, Arezki ; Aulagnier, Daniel ; Boué, François ; Brandely, Daniel ; Cognée, Philippe ; Dalbis, Eric ; Guillon, Franck ; Jammes, Louis ; Krauth, Jean Marie ; Lamy, Philippe ; Lévêque, Claude ; Mencoboni, Didier ; Mercier, Elisabeth ; Mosner, Ricardo ; Paysant, Michel ; Pierre et Gilles ; Ryan, David ; Seckler, Serge ; Sicilia, José Maria ; Talouarn, Patrick
biografie
Frans
boek